Clinical Profile of Patients with Manus Fracture Caused by Firecracker Blast - Utomo, Pamudji; Siswanto, Totok (Indonesian Journal of Medicine, 2020)
Background: Fireworks are traditionally used by various cultures or groups for celebrations. Estimated 10,000 to 12,600 people are injured because of fireworks in America every year. The type of fireworks that cause the highest injury is firecrackers with the incidence rate of 30% to 67% of all cases of injury due to fireworks. Indonesia is a country with the largest Muslim population in the world and firecrackers are often used to welcome Ramadan and Eid al-Fitr. This study aimed to report the Clinical profile of patients with manus fracture caused by firecracker blast.Case Presentation: The case study was taken from patients of Karima Utama Surgical Hospital, Surakarta, Indonesia, during Ramadan and Eid al-Fitr (from May 14 to June 15) 2018. A total of 36 patients were fractured due to firework explosions recorded in medical records during that period. Data such as gender, age and fracture diagnosis were collected in this study.Results: Males have a higher prevalence of 28 (78%) than female 8 (22%), with the highest group age between 11 to 20 years with 11 cases (31%) and more than 60 years being the lowest age group with 2 (6 %) cases of a total of 36 respondents. The right hand as the dominant hand has an injury incidence rate of 31 (86%) compared to the left hand 5 (14%) and more often occurs single fracture 22 (61%) compared to multiple fractures 14 (39%) including the amputated phalanx.Conclusion: Our study showed 36 patients had fractures of the manus due to firecrackers, with the majority of male victims 28 (78%) and single manus fractures 22 (61%) with the right-hand dominance at the age between 11 to 20 years.Keywords: manus fracture, firecrackerCorrespondence: Pamudji Utomo. Department of Orthopedics and Traumatology Prof. Dr. R. Soeharso Orthopedics Hospital, Surakarta. Email: utomodr@yahoo.com.Indonesian Journal of Medicine (2020), 05(01): 57-62https://doi.org/10.26911/theijmed.2020.05.01.09